Representasi Kresna Kecil dalam Relief Kresnayana Candi Prambanan: Kajian Ikonografi dan Narasi Visual - Fajar Persada Supandi; I Wayan Adyana; Anak Agung Gde Bagus Udayana; Alit Kumala Dewi (Universitas Budi Luhur, 2026)
The Kresnayana reliefs at Prambanan Temple present important episodes from the childhood of Krishna, yet they have received less attention compared to the well-studied Ramayana cycle. This study investigates three panels (5, 6, and 7) carved on the balustrade of Candi Wisnu, which depict the Dāmodara Līlā, the confrontation with Pūtanā, and Krishna as cowherd (Govinda). A qualitative descriptive approach was applied, integrating iconographic and visual narrative analysis. Primary data were collected through field observation and photographic documentation, while secondary data were derived from the Bhāgavata Purāṇa, Harivaṃśa, and the Old Javanese Kakawin Kresnayana. The findings show that Panel 5 reveals Krishna as both a mischievous child and divine force, Panel 6 illustrates the defeat of Pūtanā with the unique addition of Balarāma as a Javanese adaptation, and Panel 7 portrays Krishna as Govinda in relation to agrarian life. These panels form a coherent narrative arc and demonstrate how Purāṇic traditions were localized, functioning as visual pedagogy in ninth-century Java.